Synthesis And Characterization Of Some Calamitic Liquid Crystals Consisting Of Cholesterol, Rod-Like Imine And Biphenyl-4-Carboxylate Components - Ha , Sie Tiong (2006)
Sebanyak tujuh siri hablur cecair kalamitik berjaya disintesis dan dicirikan.